The positive politeness strategies used on whatsapp conversation between student and teacher in English learning at al-luthfah Islamic school - Dwi Santoso; Novita Indriani (Association for Scientific Computing Electrical and Engineering(ASCEE), 2021)
This Study discusses WhatsApp conversations between students and teachers used while learning English used in teaching activities to determine the type of politeness used by students in WhatsApp conversations during English learning at the al-Lutfah Islamic school. This research uses descriptive qualitative as the research method. The research subject is Student and teacher, while the study's object is politeness strategies in conversation WhatsApp that may contain politeness. The data of this research is the WhatsApp conversation of having politeness strategies. It uses observation and takes notes to collect the data. The data analyzing method is metode agih. The participants of this research are teachers and students at Al-Luthfah Islamic school. The transcriptions were analyzed and discussed based on the politeness of Brown and Levinson (1987). This study's findings reveal the kinds of politeness types used by Al-Luthfah Islamic students to encode politeness or politeness. In the form of several messages when replying to several statements in the WhatsApp group. These expressions are in the form of greetings, gratitude, ask questions, express opinions, and several forms of these messages are stages of obtaining data, identifying data, looking for standards, classifying types of politeness, and finding their function of the politeness used. And analyze the data.